2004
DOI: 10.1063/1.1644049
|View full text |Cite
|
Sign up to set email alerts
|

Blocking thin-film nonuniformities: Photovoltaic self-healing

Abstract: An approach is developed to block the effects of lateral nonuniformities in thin-film semiconductor structures. The nonuniformity modulates the surface photovoltage distribution. When exposed to light and immersed in a proper electrolyte, this distribution will generate laterally nonuniform electrochemical reactions. Such treatments result in a nonuniform interfacial layer that balances the original nonuniformity. This approach has been implemented for CdTe/CdS photovoltaic devices, in which it improved the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…It thus seems unlikely that the electrophoresis mechanism is correct since it fails to predict the observed difference between c-Si and a-Si:H. A second mechanism for limiting V OC might be lateral inhomogeneities in our polyaniline. An experiment on CdS/CdTe solar cells showed that blocking such inhomogeneities improved V OC and cell efficiency dramatically [16]. However, for the a-Si:H based n/i/PANI structures, we did not find saturation of V OC for the larger PANI conductivities, which seems to exclude this possibility.…”
Section: Resultsmentioning
confidence: 57%
“…It thus seems unlikely that the electrophoresis mechanism is correct since it fails to predict the observed difference between c-Si and a-Si:H. A second mechanism for limiting V OC might be lateral inhomogeneities in our polyaniline. An experiment on CdS/CdTe solar cells showed that blocking such inhomogeneities improved V OC and cell efficiency dramatically [16]. However, for the a-Si:H based n/i/PANI structures, we did not find saturation of V OC for the larger PANI conductivities, which seems to exclude this possibility.…”
Section: Resultsmentioning
confidence: 57%
“…As observed by Roussillon et al [3], following a successful treatment, the CdTe surface changes to a light gray color. Sometimes, following certain treatment conditions, an organic film can be observed on the CdTe surface.…”
Section: Resultsmentioning
confidence: 77%
“…CdTe treatments generally involve oxidizing wet chemical etches, for example Br 2 /methanol (BM) and HNO 3 /H 3 PO 4 (NP), but these often tend to be reactive, corrosive and toxic, and care is required to prevent over-etching of the CdTe surface. Recently, a new surface treatment was reported by Roussillon et al [3], where CdTe/CdS structures where treated under illumination in red wine and in aqueous solutions based on aniline (see Figure 1a for structure). Following contacting, devices treated with these solutions showed significant improvements in performance, exceeding 11% conversion efficiency, compared to devices that had not received treatment.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The other types of degradation in CdTe devices which arise from the hot spot runaway and surface nonuniformities were considered with a different approach elsewhere (e.g. thermal-electrical coupled model) and are not the subject of this study (Karpov, 2012;Karpov et al, 2013;Roussillon et al, 2004).…”
Section: Introductionmentioning
confidence: 99%